Imparting of Polar Research to the 1880’s Public - Reinhard Mook (Nordlit: Tidsskrift i litteratur og kultur, 2008)
The International Polar Year 1881/1882 marks a significant change in writing about the Arctic to the middle classes of central Europe. Up to that time many of these reports had been thrilling, dramatizing, and had glorified the own nation. Following the Polar Year, writing gradually became less emotional, more sober, induced by scientific standards. The present paper will call attention to that change.